Numerical experiments on plasma focus neutron yield versus pressure compared with laboratory experiments - Lee, S.; Saw, S. H.; Soto, L.; Springham, S. V.; Moo, S. P. (IOP Publishing, 2009)
Published literature shows that the neutron yield of the plasma focus has been modeled in two papers using a thermonuclear mechanism. However, it is more widely held that plasma focus neutrons are produced mainly by nonthermalized mechanisms such as beam–target. Moreover these papers use several parameters which are adjusted for each machine until the computed neutron yield Yn data agree with measured Yn data. For this paper numerical experiments are carried out, using the Lee model code, incorporating a beam–target mechanism to compute the Yn versus pressure data of plasma focus devices PF-400 J and FN-II. The Lee model code is first configured for each of these two machines by fitting the computed current waveform against a measured current waveform. Thereafter all results are computed without adjusting any parameters. Computed results of Yn versus pressure for each device are compared with the measured Yn versus pressure data. The comparison shows degrees of agreement between the laboratory measurements and the computed results.